Backbone NMR assignments of tryparedoxin, the central protein in the hydroperoxide detoxification cascade of African trypanosomes, in the oxidized and reduced form - Wagner, Annika; Krauth-Siegel, Renate (Biomolecular NMR assignments, 2017)
Tryparedoxin (Tpx) is a pivotal protein in the redox-metabolism of trypanosomatid parasites. Tpx has previously been identified as a potential target for drug development in the fight against human African sleeping sickness caused by Trypanosoma brucei. Tpx belongs to the thioredoxin superfamily and acts as an oxidoreductase in the parasite’s cytoplasm. It contains a WCPPC active site motif, which enables the protein to undergo thiol-disulfide exchange. To promote future protein-drug interaction analyses, we report the 1H, 13C and 15N backbone chemical shift assignments for both the oxidized and reduced states of Tpx. The redox state of the protein has a significant impact on the chemical shifts of the residues at the active site of the protein, especially on the two redox active site cysteines. The NMR assignments presented here will be a prerequisite for investigating drug binding to Tpx in molecular detail and to drive further drug optimization.
Published online: 1 June 2017
Gesehen am 06.07.2018